Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di Rumah Sakit Islam Siti Rahmah Kota Padang - Hanum, Novia Zulfa; Yusman, Rahmanita; Rahmadianti, Yori (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
In the Minister of Health Regulation Number 66 of 2016, concerning occupational health and safety in Hospitals, a hospital is a workplace with a high risk of safety and health. In addition, in the context of managing and controlling risks related to occupational health and safety in hospitals, it is necessary to organize occupational health and safety in hospitals to create hospital conditions that are healthy, safe, and comfortable. The occupational health and safety reported there was still an accident occur at the Siti Rahmah Islamic Hospital. This study was to overview the implementation of the occupational health and safety management system (OHSMS) at Siti Rahmah Islamic Hospital in 2020. This research was a qualitative descriptive study with an in-depth interview and observation approach conducted at Siti Rahmah Islamic Hospital from January to December 2020. The population is all workers registered as employees at Siti Rahmah Islamic Hospital. Informants in this research were those who have the authority and knowledge about the immplementation of the occupational health and safety management system (OHSMS) in Siti Rahmah Islamic Hospital. Concerning the preparation, implementation, monitoring, and evaluation of the occupational health and safety management system (OHSMS) have not been implemented optimally. It is expected that Siti Rahmah Islamic Hospital implemented of occupational health and safety management system (OHSMS) optimally.